Factors Associated with the Patient Safety Activities among Home-Visit Caregiver: A Cross-Sectional Study - Soon-hee Cho; Sujin Kang; Youngji Kim (Annals of Geriatric Medicine and Research, 2025)
Background Home-visit care should prioritize patient safety and promote positive safety awareness to maintain caregivers' commitment to providing safe care. This descriptive study aims to examine the relationship between home-visit caregivers' knowledge, attitudes, awareness of patient safety, and safety-related activities. Methods The participants were 210 adult home-visit caregivers, aged 20 years or older, with more than six months of experience working at six long-term care centers in Daejeon Metropolitan City. Data were collected using a structured self-report questionnaire to measure participants’ general characteristics and their patient safety knowledge, attitudes, awareness, and activities, and analyzed using SPSS/WIN version 28.0. Results This study demonstrated that patient safety activities were significantly positively correlated with patient safety knowledge (r=0.63, p<0.001), patient safety attitude (r=0.49, p<0.001), and patient safety awareness (r=0.69, p<0.001). The factors affecting patient safety activities were patient safety awareness and patient safety knowledge, with an explanatory power of 55%. Conclusion To practice patient safety activities and maintain a desirable attitude, an educational strategy that promotes cognitive change, such as a systematic and continuous practice-oriented campaign, is needed. Furthermore, efforts to improve the working environment to extend the tenure of experienced caregivers are required.